Budaya Carok dan Rekonstruksi Nilai Pendidikan Masyarakat Madura - Alatas, Moh. Muhsin; Wahyuni, Amalia Desy (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
The Carok culture that has existed within Madurese society has often been perceived as an expression of violence and moral transgression. However, behind this representation lies a complex system of values, worldviews, and moral structures that reflect the cultural identity of Madurese society. This study aims to explore the meaning and moral values in the Carok culture through etymological and epistemological approaches, as well as to reconstruct the potential of these values as a source of learning in local culture-based moral education. This study uses a literature review method by examining various scientific sources, such as anthropological research results, ethnographic studies, literary works, and moral education theories. The analysis was conducted thematically and interpretively to identify the dimensions of knowledge (episteme) and the origins of meaning (etymon) of the Carok culture. The synthesis results show that Carok is essentially a symbol of honor (self-esteem), responsibility, and the defense of family values born from the Madurese community's ethical system. These values have significant relevance in the development of contextual moral education based on local wisdom. This study confirms that moral education cannot be separated from the cultural roots of society; on the contrary, local cultures such as Carok can be an epistemological source for character building and ethical understanding in modern education